1-D mathematical modeling of a diesel oxidation catalyst for transient hot start drive cycle. Issue 4 (August 2020) - Nair, Sreeharsh; Mittal, Mayank
Abstract: The need to obey with increasingly stringent emission regulations has amplified the importance of after treatment devices, and therefore, reliable tools need to be developed for the evolution of better aftertreatment devices. Even though the upcoming regulations paved the way for improved combustion engines, their high carbon monoxide and hydrocarbon emissions increased the load on catalytic converters. Numerical modeling is one such tool which is extremely useful in providing the basic information which helps in designing the reactor, understanding its operation, and predicting the performance. In this context, the utmost aim of the numerical modeling is to simulate the driving cycle where inlet conditions to the catalytic converter vary with respect to time. Such a simulation must include the calculations of transient temperature-field of the monolith substrate and converter-out mass emissions. In this paper, a one-dimensional mathematical modeling of an oxidation catalyst has been implemented to simulate a hot start New European Drive Cycle (NEDC). The transient engine data was taken from the literature, and the measured instantaneous traces at the outlet of the catalyst were compared with the model predictions. This model has been developed to investigate the CO conversion performance of the catalyst. The comparison between model predictions and experiments has shown a satisfactory agreement in terms of both substrate temperature and CO emission at the catalyst outlet, confirming the effectiveness of the methodology applied. The reliability of the 1-D model was also proved with the probability density function of the conversion efficiency.